Prevalence and risk factors for gastrointestinal parasites in small-scale pig enterprises in Central and Eastern Uganda - Roesel, Kristina; Dohoo, I.; Baumann, M.; Dione, Michel M.; Grace, Delia; Clausen, Peter-Henning (Springer, 2017)
In Eastern Africa, small-scale pig keeping has emerged as a popular activity to generate additional household income. Infections of pigs with gastrointestinal helminths can limit production output, increase production costs, and pose zoonotic risks. A cross-sectional, community-based study in three districts in Eastern and Central Uganda examined the prevalence of gastrointestinal helminthes and associated risk factors in 932 randomly sampled pigs. Using the combined sedimentation-flotation method, 61.4 % (58.2–64.5 %, 95 % confidence interval [CI]) tested positive for one or more gastrointestinal helminths, namely, strongyles (57.1 %, 95 % CI), Metastrongylus spp. (7.6 %, 95 % CI), Ascaris suum (5.9 %, 95 % CI), Strongyloides ransomi (4.2 %, 95 % CI), and Trichuris suis (3.4 %, 95 % CI). Coccidia oocysts were found in 40.7 % of all pigs sampled (37.5–44.0 %, 95 % CI). Significant differences across the three districts were observed for the presence of A. suum (p < 0.001), Metastrongylus spp. (p = 0.001), S. ransomi (p = 0.002), and coccidia oocysts (p = 0.05). All animals tested negative for Fasciola spp. and Balantidium coli. Thirty-five variables were included in univariable analyses with helminth infection as the outcome of interest. A causal model was generated to identify relationships among the potential predictors, and consequently, seven variables with p ≤ 0.15 were included in a multivariable analysis for helminth infection. The final regression models showed that routine management factors had a greater impact on the prevalence of infection than regular, preventive medical treatment or the level of confinement. Factors that negatively correlated with gastrointestinal infection were the routine removal of manure and litter from pig pens (p ≤ 0.05, odds ratio [OR] = 0.667) and the routine use of disinfectants (p ≤ 0.05, OR = 0.548).